2018
DOI: 10.1007/s00421-018-3807-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between power–duration parameters and mechanical and anthropometric properties of the thigh in elite cyclists

Abstract: In addition to muscle size, the maximal evocable force of a muscle (group) appears to be linked to the magnitude of the W' in elite cyclists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 43 publications
0
37
1
Order By: Relevance
“…Unfortunately, the optimum protocol for evoking training improvements in D′ still remain elusive. The link between D′ and thigh circumference [20], as well as the considerably larger D′ values discovered in high-level male rugby players [21], provide some enticing insights related to the potential mechanisms by which D′ may be enhanced. Notwithstanding, the fact that the cycling equivalent of D′ (termed W′) may be potentiated with creatine supplementation [24,36], and that the W′ kinetics may be modelled on the basis of PCr kinetics [18], hints at a peripheral fatigue connection that seems to be associated with the VO 2 slow component that develops when intensities exceed CS/CP [29].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Unfortunately, the optimum protocol for evoking training improvements in D′ still remain elusive. The link between D′ and thigh circumference [20], as well as the considerably larger D′ values discovered in high-level male rugby players [21], provide some enticing insights related to the potential mechanisms by which D′ may be enhanced. Notwithstanding, the fact that the cycling equivalent of D′ (termed W′) may be potentiated with creatine supplementation [24,36], and that the W′ kinetics may be modelled on the basis of PCr kinetics [18], hints at a peripheral fatigue connection that seems to be associated with the VO 2 slow component that develops when intensities exceed CS/CP [29].…”
Section: Discussionmentioning
confidence: 95%
“…Progressive overload was implemented by adjusting the work speed by approximately 5% per week as tolerated. For each session and for each participant the heart rate (Polar H7, Polar, Kempele, Finland), speed (Stryd, Bolder, USA) and rating of perceived exertion (RPE; Borg [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]) were continuously monitored and recorded. For safety, we set a speed-limit of 4.44-5.00 m/s depending on the speed tolerance of the individual.…”
Section: Hiit Program Designmentioning
confidence: 99%
“…Firstly, the cyclists assumed their race cycling‐specific position, on a custom‐built ergometer that had the cast flywheel clamped, to ensure the cranks were stationary. In this position, architecture of the vastus lateralis (ie, pennation angle [Pθ VL ] and fascicle length [FL VL ]) was assessed at rest prior to exercise using ultrasound . Subsequently, the cyclists had surface electromyography (EMG) electrodes placed on three muscles of both legs (gluteus maximus [GM], biceps femoris long head [BF], and vastus lateralis [VL]) and mounted another custom‐modified isovelocity ergometer (again, the position mirrored their racing position).…”
Section: Methodsmentioning
confidence: 99%
“…This might account for the lack of a correlation between W′ and skeletal muscle fibre type reported in the current study and elsewhere(43) and suggests that W′ might be more closely linked to other physiological events. For example, a recent study has demonstrated, in a group of elite track cyclists, that W′ is positively correlated with the maximum force generating capacity of the knee extensors and gross thigh volume(24).Clearly, further research is required to resolve the physiological bases of W′.This investigation has demonstrated very strong positive correlations between critical power (CP) and skeletal muscle capillarity, particularly in relation to type I fibers, in endurance trained individuals. Moreover, CP was positively correlated with type I skeletal muscle fiber proportion and CSA.…”
mentioning
confidence: 86%